Does Bisphosphonate Increase the Sclerosis of Tibial Subchondral Bone in the Progression of Knee Osteoarthritis—A Propensity Score Matching Cohort Study Based on Osteoarthritis Initiative - Li, Mingyang; Nie, Yong; Zeng, Yi; Wu, Yuangang; Liu, Yuan; Wu, Limin; Xu, Jiawen; Shen, Bin (Frontiers in Medicine, 2021)
Bisphosphonate has great potential in KOA therapy, but whether the anti-resorption mechanism of bisphosphonate aggravates sclerosis of subchondral bone remains unclear. We found that bisphosphonate use did not increase sclerosis of subchondral bone in established KOA, perhaps resolving some concerns about bisphosphonate in patients with KOA. Introduction: Most studies have focused on the protective effect of bisphosphonate on early knee osteoarthritis (KOA) through its anti-resorption mechanism in osteoclasts. However, late KOA has a decreased rate of resorption, which is the opposite of early KOA. The risk of subchondral bone sclerosis in late KOA after using bisphosphonate has not been investigated using morphometry. Methods: Forty-five patients who had ever used bisphosphonate (or 33 patients with current use) were matched with controls through propensity matching methods, including age, body mass index (BMI), sex, health status (12-Item Short Form Survey physical health score), physical activity level (Physical Activity Scale for the Elderly score), vitamin D use, and calcium use. At the baseline and 12-month (or 18-month) follow-up, bone mineral density (BMD) of the tibia and hip was measured by dual-energy X-ray absorptiometry (DXA), and medial tibial subchondral bone morphometry: bone volume fraction (BV/TV), trabecular thickness (Tb.Th), trabecular number (Tb.N), and trabecular separation (Tb.Sp) were calculated based on 3-T trabecular MRI. Data were obtained from the Bone Ancillary Study in the Osteoarthritis Initiative (OAI) project. Results: The yearly percentage change in hip BMD of the current bisphosphonate-use group was significantly greater than that of the non-bisphosphonate-use group (0.7% vs. −1%, P = 0.02). The other outcomes (BV/TV, Tb.N, Tb.Sp, Tb.Th, tibia medial BMD, and tibia lateral BMD) between the two groups presented no significant difference. The non-bisphosphonate-use group experienced a significant increase in Tb.Th [2%, 95% CI = (1%, 4%), P = 0.01], while the bisphosphonate-use group presented no significant change [1%, 95% CI = (−2%, 4%), P = 0.54]. Conclusions: Bisphosphonate use did not increase sclerosis of subchondral bone in established KOA. Bisphosphonate might have a stage-dependent effect on subchondral bone in KOA initiation and progression.